2021
DOI: 10.1002/mrm.28763
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve intratrain prospective motion correction for turbo spin‐echo sequences with constant flip angles

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Several methods have been proposed to obtain the uncorrected images in order to assess the performance of PMC, including multiple scans with PMC-enabled anddisabled [10][11][12][13][14][15][16], single scan with interleaved acquisition of PMC-enabled anddisabled [17], and motion artifact simulation [18]. However, to evaluate the effectiveness of PMC in routine clinical studies, only motion artifact simulation is feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been proposed to obtain the uncorrected images in order to assess the performance of PMC, including multiple scans with PMC-enabled anddisabled [10][11][12][13][14][15][16], single scan with interleaved acquisition of PMC-enabled anddisabled [17], and motion artifact simulation [18]. However, to evaluate the effectiveness of PMC in routine clinical studies, only motion artifact simulation is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the motion-induced artifacts, two widely used schemes including retrospective motion correction (RMC) [5][6][7][8][9] and prospective motion correction (PMC) have been reported [10][11][12][13][14][15][16][17][18]. An earlier study [5] using fat navigators (FatNav) to estimate motion profile has found the beneficial effects of RMC on measuring PVS visibility and physiological changes.…”
Section: Introductionmentioning
confidence: 99%
“…First, while the framework corrects for motion between the LR multislice images, intraand inter-slice motion is not yet accounted for. To compensate for intraslice motion, our framework could be combined with prospective motion correction strategies (Gao et al, 2021;Maclaren et al, 2013). Furthermore, inter-slice motion could be accounted for by adding motion parameters for each individual slice of the LR images and estimating these parameters jointly with the HR tissue parameter maps.…”
Section: Discussionmentioning
confidence: 99%
“…The dual‐contrast sequence could be designed to share echoes 42 to reduce TA while maintaining production of PD‐weighted and T 2 ‐weighted base images, with extension to multi‐echo methods for further quantitative measures (such as T 1 ). Techniques to alleviate intrascan motion have recently been proposed for constant flip angle train FSE sequences 43 and will be investigated for variable flip angle trains in future work.…”
Section: Discussionmentioning
confidence: 99%